Implementación de una Carta de Control para Corridas Cortas en la Industria de Autopartes - Barrera Cobos, Jesús Fidernan (Ingeniería, 2016)
Context: The national industry has to adapt to market needs, which implies the change in the performance of their production processes. One of these changes has to do with the size of production lot, which has gone from a size of one thousand units of perhaps a few hundred. The monitoring of these processes using statistical methods such as control charts, has led to the use of so-called control charts for short runs. Method: This article presents the proposed implementation of a chart of this type in a manufacturing process of a company in the national automobile sector. Initially the current state of the process poses with the results shown in the control chart X¯–R, used by the company to monitor production; then the mention of some of the control charts for short production runs that can be used for this type of variables which have been raised by various authors is made. Results: Based on the information of the current status process the election of the chart is made more suitable for short production runs. Conclusions: Given the characteristics of non-homogenity of variance, determined by a nonparametric test for references analyzed, it is decided that the letter to be used is the normalized chart. The decision of which chart to use depends on the variance of the process to manufacture the various references.